The network that bounced back - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Now here s a simple, straightforward story of success. The Agridoc network started in France just over 20 years ago, and for years provided a sound but basic service distributing documents about agriculture, principally to francophone Africa. Many...